2020
DOI: 10.1002/adem.202000430
|View full text |Cite
|
Sign up to set email alerts
|

Developing a New Beta‐Type of Ti–Si/Sn Alloys for Targeted Orthopedic Therapeutics: Assessments of Biological Characteristics

Abstract: Titanium (Ti) alloys are widely used in tissue engineering, but their applications are limited by low strength, bactericidal properties, and metal ion release. Beta Ti alloys are promising materials for load‐bearing orthopedic implants due to their excellent corrosion resistance and high biocompatibility. Herein, developed new beta‐Ti alloys including Ti–Nb–Zr–Sn (Ti–Sn) and Ti–Nb–Zr–Ta–Si (Ti–Si) to improve structural and biochemical features of the existing Ti alloys as orthopedic implants. The new Ti–Sn and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…One approach to improving the stability of the resultant alloy that this study does not look at is the final finish of the material as well as manufacturing techniques to obtain the best result. For corrosion resistance, we only consider the oxide scale formed by the alloy, however methods such as ceramic coating and/or mechanical polishing have been shown to work in conjunction with the oxide scale to further improve corrosion resistance [64][65][66]. More advanced manufacturing practices such as a sputtering process can alter the oxide scale to obtain a more favorable phase ratio [67].…”
Section: Systemmentioning
confidence: 99%
“…One approach to improving the stability of the resultant alloy that this study does not look at is the final finish of the material as well as manufacturing techniques to obtain the best result. For corrosion resistance, we only consider the oxide scale formed by the alloy, however methods such as ceramic coating and/or mechanical polishing have been shown to work in conjunction with the oxide scale to further improve corrosion resistance [64][65][66]. More advanced manufacturing practices such as a sputtering process can alter the oxide scale to obtain a more favorable phase ratio [67].…”
Section: Systemmentioning
confidence: 99%
“…
Ti alloys were widely used in aerospace, energy, and biomedical industries thanks to their high strength-to-density ratio, good fatigue performance, and excellent corrosion resistance. [1][2][3][4] Among them, metastable β-Ti alloys have gained increasing attention in recent years because of their variety of deformation modes. [5][6][7][8] It has been reported that the stability of the β phase was a function of chemical composition, which strongly influenced the deformation modes.
…”
mentioning
confidence: 99%